Effects of Supplementation with Corn or Dried Distillers Grains on Gains of Heifer Calves Grazing Smooth Bromegrass Pastures - L. W. Lomas; J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2019)
A total of 150 heifer calves grazing smooth bromegrass pastures were used to compare supplementation with 0.5% of body weight per head daily of corn or dried distillers grains (DDG) in 2014, 2015, 2016, 2017, and 2018. Daily gains of heifers supplemented with corn or DDG were similar (P>0.05) in all years except 2018, when heifers supplemented with DDG had greater (P<0.05) gains than those supplemented with corn.
Keywords: corn; distillers grains; grazing; smooth bromegrass; supplementation; stocker cattle; heifers